Analysis of Student’s Misconception and Intrinsic Motivation in the Online-Collaborative Learning - Galuh Catur Wisnu Prabowo; Gamilla Nuri Utami; Alvina Miranda (Universitas Lampung, 2022)
Abstract: Analysis of Student’s Misconception and Intrinsic Motivation in the Online-Collaborative Learning. Collaborative learning in the pandemic situation has some problems to be solved, especially in learning processes. This is done to analyze students’ misconceptions and motivations during online learning. The aim of the study was to assess the collaboration process in online learning by using jumping tasks. This is a descriptive research method using the lesson study approach in SMPN 7 Bandarlampung, meanwhile the subject is the student of grade 7. The instruments of research were used observation sheet and questionnaire. Based on the results of observations of the level of confidence of students associated with misconceptions in the material provided, many students answered confidently but did not understand the concept. Misconceptions occurred not only in students who answered incorrectly and with high confidence, but also in students who answered correctly with the wrong reason. This means that students only did (wild guess) or guess with origin. In a nutshell, the provision of jumping tasks in collaborative learning has not been able to minimized the occurrence of the misconception and show the intrinsic motivational in moderate and high level.Keywords: Misconception, Motivation, Collaborative Learning